Multi-scale modelling of diffusion magnetic resonance imaging in heterogeneous media - Lau, C-T (2022)
Diffusion magnetic resonance imaging (diffusion MRI) is an imaging technique which is sensitive to the micrometre scale movement of water molecules within a medium. It is routinely used in clinical practice, as well as increasingly in biomedical research as a quantitative tool. However, mathematical relations describing the image signal in a heterogeneous medium are poorly established. There is therefore a need for a better mathematical foundation for diffusion MRI which accounts for the heterogeneous nature of biological tissue, both in terms of molecular transport and magnetic properties.